1996
DOI: 10.1146/annurev.micro.50.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Osmoadaptation by Rhizosphere Bacteria

Abstract: The osmolality of rhizosphere soil water is expected to be elevated in relation to bulk-soil water osmolality as a result of the exclusion of solutes by plant roots during water uptake, the release of plant root exudates, and the production of exopolymers by plant roots and rhizobacteria. In contrast, the osmolality of water within highly hydrated bulk soil is low (less than 50 Osm/kg); thus the ability to adapt to elevated osmolality is likely to be important for successful rhizosphere colonization by rhizoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
210
1
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(232 citation statements)
references
References 152 publications
12
210
1
5
Order By: Relevance
“…A higher growth of roots than shoot of the inoculated plants and a highly significant positive correlation of all the root growth parameters (except number of seminal roots) with dry mass and water insoluble soil saccharides content of the RS (Table 4) indicated that influence of the RS factors on growth of roots was more prominent and stronger than a decrease in Na + uptake by inoculated wheat plants. Since the EPS-producing bacteria were isolated from the saltaffected soils and were adapted to the salts stress (Miller, et al, 1996), their inherent salt tolerant capability helped the plants to withstand initial effect of osmotic stress (Munns, 2002). Moreover, a higher EPS-producing bacterial population harboured initially on roots of the inoculated than un-inoculated plants was enable to stimulate and enhance the extent of the root exudates (Tisdall, 1994;Miller, et al, 1996;Wittenmayer and Merbach, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A higher growth of roots than shoot of the inoculated plants and a highly significant positive correlation of all the root growth parameters (except number of seminal roots) with dry mass and water insoluble soil saccharides content of the RS (Table 4) indicated that influence of the RS factors on growth of roots was more prominent and stronger than a decrease in Na + uptake by inoculated wheat plants. Since the EPS-producing bacteria were isolated from the saltaffected soils and were adapted to the salts stress (Miller, et al, 1996), their inherent salt tolerant capability helped the plants to withstand initial effect of osmotic stress (Munns, 2002). Moreover, a higher EPS-producing bacterial population harboured initially on roots of the inoculated than un-inoculated plants was enable to stimulate and enhance the extent of the root exudates (Tisdall, 1994;Miller, et al, 1996;Wittenmayer and Merbach, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Since the EPS-producing bacteria were isolated from the saltaffected soils and were adapted to the salts stress (Miller, et al, 1996), their inherent salt tolerant capability helped the plants to withstand initial effect of osmotic stress (Munns, 2002). Moreover, a higher EPS-producing bacterial population harboured initially on roots of the inoculated than un-inoculated plants was enable to stimulate and enhance the extent of the root exudates (Tisdall, 1994;Miller, et al, 1996;Wittenmayer and Merbach, 2005). Thus in consequence to intensive release of the plant root exudates in the rhizosphere, the EPS-producing bacterial population was increased further and the extent of EPS synthesis was fostered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. maltophilia isolates could grow well at 5 % NaCl, whereas for members of the B1 group, 4n5 % was the highest salinity allowing growth. Tolerance to high and changing salinities is important for adaptation in both microenvironments (the rhizosphere and the human body) (Miller & Wood, 1996). All strains of Stenotrophomonas synthesized trehalose, but only strains of the B1 group accumulated glucosylglycerol as an additional substance.…”
Section: Physiological Aspects and Fatty Acid Compositionmentioning
confidence: 99%
“…Osmoadaptation also induces remodelling of the cell envelope and cell surface structures i.e. membrane or periplasmic protein composition, lipid composition, periplasmic glucan level and EPS synthesis (Miller & Wood, 1996). Ultimately, some of these modifications could lead to biofilm (or aggregate) formation (Karatan & Watnick, 2009).…”
Section: Discussionmentioning
confidence: 99%